An investigation of how context affects the response of pedestrians to the movement of others. (January 2023) - Tong, Yunhe; Bode, Nikolai W.F.
Abstract: Identifying how pedestrians respond to the movement of others in emergencies is an essential topic that is directly relevant to building evacuation and safety management. Here, we hypothesise that pedestrian following behaviour depends on the context. We identify three essential contextual factors: spatial information, the size of crowds and the distribution of individuals across exits. We conduct a virtual experiment with over 500 participants who have to decide whether to follow a crowd in scenarios capturing these different contextual factors. Our findings suggest pedestrians have an innate preference to avoid the exit chosen by a majority of people but also that they prefer exits that are associated with shorter escape routes, even if these exits are used by more people. However, if one exit is not used at all, these preferences are altered and pedestrians prefer following others regardless of exit properties. In contrast to the relative usage of exits, the overall size of the crowd does not affect pedestrian exit choice in our experiment except for the case when all pedestrians choose the same exit. We call the change in exit choice behaviour depending on how pedestrians are distributed across exits "split effect". Simulation results show how the split effect can lead to unbalanced route usage and reduce the efficiency of pedestrian flow in certain circumstances, such as when the arrival rate of pedestrians is low. Our work adds to a growing body on pedestrian exit choice and highlights the importance of precise control of contextual factors in research. Highlights: An experiment on how pedestrians' responses to others' movement depends on the context. In our experiment pedestrians have an innate tendency to avoid crowds. When spatial information is available, it influences pedestrian route choice more than the crowd. Pedestrians avoid an absolutely empty exit even if it otherwise has desirable properties. This may lead to unbalanced route usage and reduce the efficiency of pedestrian flow.